The Criminal Offence Of Corruption Of Village Funds (Analysis Of Medan District Court Decision No. 59/Pid.Sus-Tpk/2019 /Pn Mdn) - Radyansyah Fitrianda Lubis; Edi Yunara; Mirza Nasution; Marlina , Marlina (Fakultas Hukum Universitas Muhammadiyah Sorong, 2024)
This research aims to provide an understanding of the legal aspects of Village Fund Corruption. In detail, the objectives to be achieved are to analyze the Legal Regulation of the Crime of Corruption of Village Funds, the process of supervision of Village Funds in an effort to prevent Corruption Crimes in Batu Bara Regency and the Legal Considerations of Judges in Issuing Verdicts on Corruption Crimes of Village Funds in the Decision of the Medan District Court No.59/Pid.Sus-TPK/2019/PN Mdn.This study uses a statutory approach and a case approach in its normative juridical research methodology. The results of the study show that the Criminal Law Regulation on the Crime of Corruption of Village Funds, is contained in Law Number 31 of 1999 jo Law Number 20 of 2001 concerning the Eradication of Corruption Crimes, especially articles 2 and 3. The mechanism for monitoring village funds requires the involvement of all parties, namely the village community, the Village Consultative Body (BPD), the Government Internal Supervisory Apparatus (APIP), and related OPDs. The judge's decision is very important, because in it there is a value that can be in direct contact with human rights. In principle, only the judge's decision that has permanent legal force can be implemented. A decision can be said to have permanent legal force if it is issued through an open and transparent trial and no other legal remedies are submitted. Regulation of Village Fund Corruption is regulated in Law Number 31 of 1999 jo Law Number 20 of 2001 concerning the Eradication of Corruption Crimes articles 2 and 3. In carrying out the supervised supervision of village funds, the involvement of all parties is needed, and the judge's decision is very important, because in it there is a value that can be in direct contact with human rights.